What are the kinematic characteristics of the world champion couple in competitive ballroom dance during the waltz's spin movement? - Yoshida, Yasuyuki; Bizokas, Arunas; Demidova, Katusha; Nakai, Shinichi; Nakai, Rie; Nishimura, Takuichi (Frontiers in Sports and Active Living, 2022)
To evaluate competitive ballroom dancing, one of the official events of the World Games, spin movements used by advanced dancers who ranked high in actual competition may be employed. The purpose of this study was to investigate the kinematic characteristics of spin movements in competitive ballroom dancing performed by world champion couples, especially holding posture and lower limb movements. A champion couple and 13 national-level competitive ballroom dancers as the control group participated in this study. An inertial measurement unit (IMU) system (MVN Link; Xsens, Netherlands) consisting of 17 IMUs, attached to feet, shanks, thighs, pelvis, sternum, head, upper arms, forearms, and hands of the dancers, was used to obtain three-dimensional kinematic data at 240 Hz. The overall trend was that the actual and normalized stride lengths of the champion male and female dancers tended to be longer than those of the male and female dancers in the control group. Further, large differences were observed in the pelvic and rib cage segments movements, and the relative angle of the rib cage segment to the pelvic segment. The champion male dancer started to move from the pelvic segment, whereas the champion female dancer and the national-level top male and female dancers started to move from the rib cage segment. During the spin movement, the champion male dancer was in a position where the rib cage segment was rotated to the left with respect to the pelvic segment, whereas the other dancers were in a position where the rib cage segment was rotated to the right. Although limited to technical aspects, these dance kinematic characteristics of the world champion couples and their differences from those of the control group dancers, will be helpful to competitive ballroom dancers and coaches in their daily practice.